An in situ electron donor consumption strategy for photoelectrochemical biosensing of proteins based on ternary Bi2S3/Ag2S/TiO2 NT arrays. Issue 7 (9th January 2018) - Wang, Bing; Cao, Jun-Tao; Dong, Yu-Xiang; Liu, Fu-Rao; Fu, Xiao-Long; Ren, Shu-Wei; Ma, Shu-Hui; Liu, Yan-Ming
Abstract : An ascorbic acid oxidase–ascorbic acid bioevent-based electron donor consumption mode is introduced into the PEC bioassay for the first time. Abstract : An ascorbic acid oxidase (AAO)–ascorbic acid bioevent-based electron donor consumption mode was introduced into the PEC bioassay for the first time. Ternary hybrid bismuth sulfide/silver sulfide/TiO2 nanotube arrays as the photoelectrode coupled with AAO attached to SiO2 as a dual signal quenching strategy were employed for sensitivity enhancement.